(untitled) (SAARC Journal of Agriculture, 2014)
Pullorum disease is caused by Salmonella enterica subspecies enterica serovar Pullorum. Chickens are the natural host of this pathogen. In the present study experimental pathogenesis was studied. Twenty pullets (Salmonella pullorum seronegative) of Isa Brown breed of 18 weeks and 10 cocks (Salmonella pullorum seronegative) of RIR breed of 26 weeks of age were experimentally infected orally with 2 x107 (CFU) dose of Salmonella Pullorum organisms and in control group no bacteria was given. Birds were observed for clinical signs, gross pathology, and reisolation of S. Pullorum from different organs and blood, histopathological study, detection of antibody levels and detection of S. Pullorum by PCR at different time intervals of experimental period. Four hens and one cock were randomly selected and sacrificed on 6 hr before inoculation and 1 wk, 2, 3 and 4 wks of post infection (PI). Samples were collected for bacteriological, serology and histopathological examinations. Liver, lungs, ovarian follicles and testis were also collected in 50% buffered- glycerol and preserved in - 80&edeg;C for PCR. The clinical signs of infected hens were found at 72 hrs of PI, which continued up to 4 wks. 15.81% reduction in egg production was observed. The highest mean CFU ml-1 of Salmonella Pullorum from blood was 13.55x 103 at 1 wk PI and the lowest was 13x 102 at 4 wk PI. Gross lesions were variable in different birds at different time interval. The highest gross lesion was 93.75% as swollen and congested spleen and the lowest lesion was 43.75% as pericarditis and necrotic foci/ nodules in the heart. Microscopically, the liver showed congestion; hepatitis with infiltration of inflammatory cells, and focal necrosis with nodule formation. The antibody titre increased gradually and the highest titer was at 4 wks PI in hens (4712±1851) than that of cock (3059±903). S. Pullorum was detected by PCR in all liver and lung samples from 1 wk to 4 wks PI. S. Pullorum was reisolated from male and female reproductive organs after experimental infection. S. Pullorum was detected by PCR at 1 wk to 3 wks PI from testicular tissues. S. Pullorum was also reisolated from 50% eggs of experimentally infected birds. DOI: http://dx.doi.org/10.3329/sja.v11i2.18398 SAARC J. Agri., 11(2): 1-16 (2013)